Kualitas SDM, Kepemimpinan Transformasional, Kepatuhan Etik, dan Lingkungan Kerja terhadap Efektivitas Reformasi Kultur Polri - Lubis, Rahmadsyah; Nartasari, Diah Rani (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of human resource quality, transformational leadership, ethical compliance, and work environment on the effectiveness of cultural reform in the Indonesian National Police (Polri). Organizational culture transformation is a strategic priority to enhance professionalism, integrity, and responsiveness of police officers to public needs. The study employs a literature review method, analyzing 50 scholarly articles, national and international journals, and official Polri reports over the last ten years (2015–2025). The findings indicate that high HR quality, including technical, managerial, and socio-cultural competencies, significantly contributes to cultural reform effectiveness. Transformational leadership plays a critical role in motivating, inspiring, and guiding officers to consistently implement the new organizational culture. Furthermore, ethical compliance serves as a key pillar fostering integrity and transparency, while a supportive work environment facilitates competence development and collaboration among units. The integration of these four variables creates synergy that enhances the success of Polri’s cultural reform. The literature also highlights that visionary leadership and reinforcement of organizational values can reduce resistance to change. The practical implications of this study suggest continuous investment in HR training, strengthening transformational leadership, enforcing professional ethics, and improving the work environment. These findings provide a foundation for policymakers to design more effective, adaptive, and sustainable cultural reform strategies, enabling Polri to improve public service quality and public trust significantly.